Impact of Dysmenorrhea and Health-seeking Behavior among Female Adolescents - Erni Gustina; Sitti Nur Djannah (International Journal of Public Health Science (IJPHS), 2017)
Dysmenorrhea is one of common health problems to occur during menstrual period and influences women life quality. The aim of the study is to know the effect of dysmenorrhea and health-seeking behavior to teenage girl. This study belongs to observation analytic using cross sectional design. The sample is girls, which is as many as 188, at the age of 15 to 19. The data are taken through questionnaire containing several questions, such as age of the respondents, age of menarche, effect dysmenorrhea, attitude on dysmenorrhea, and health-seeking behavior. Bivariate analysis is used Chi Square test. The Prevalence of dysmenorrhea is 68.8%. The effect of dysmenorrhea to girls include the absence from school (9.6%), sleep disorders (25%), decreased appetite (25.5%), inability to do exercise (19.7%), and daily activity disruptions (9.6%). There was relationship between the attitude on dysmenorrhea and health-seeking behavior of female adolescents (p=0.029). Adolescents with positive attitude about menstrual problems will develop good health-seeking behavior during menstrual period compared to those who have negative attitude. The needs to design reproduction health program as well as updating the information to create girls awareness on their health management during dysmenorrhea are necessary.